Global Imagination and Agency Formation of Filipino Marriage Migrant Women in South Korea - Lacaba, Mahgie Bual (Archīum Ateneo, 2018)
The Filipino marriage migration to Korea has changed the conventional diaspora of Filipino migration. As many academic researchers point out that the emergence of this migration pattern is driven by the economic reasons especially of the brides from developing countries like the Philippines to more developed ones like South Korea, this research explores on the influence of what Arjun Appadurai called “global imagination” on Filipino women’s agency in choosing Korea as a “site of desire” for marriage migration. This study argues that first, Filipino marriage migration cannot only be explained with regard to the economic paradigm as it only reflects one aspect of the global imagination. Second, marriage migration as a manifestation of a woman’s self-determination or agency is widely affected by global imagination. Lastly, women should be seen as agents who are capable of exercising their own agency producing favorable outcomes along with some unfavorable ones.